2021
DOI: 10.1186/s12951-021-00933-1
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of oxidative stress with lycorine and gold-based nanocomposites for synergistic cascade cancer therapy

Abstract: Background Despite advances of surgery and neoadjuvant chemotherapy during the past few decades, the therapeutic efficacy of current therapeutic protocol for osteosarcoma (OS) is still seriously compromised by multi-drug resistance and severe side effects. Amplification of intracellular oxidative stress is considered as an effective strategy to induce cancer cell death. The purpose of this study was to develop a novel strategy that can amplify the intracellular oxidative stress for synergistic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…It is worth mentioning that the in vivo experimental results showed that the RGD-Bi2S3 @MSN/DOX NPs synthesized by Liu et al combined with nearinfrared radiation can effectively ablate malignant OS and prevent its recurrence (66). Similarly, Hu et al developed a new type of mesoporous silica-coated gold nanostar (GNS@ MSNs-FA) modified by folic acid (FA) with the Chinese medicine lyricine (Ly) NPs (67). In summary, the researchers utilized gold nanostars (GNS) with multiple sharp branches as the core of the nanocomposite, employing MSNs to coat the core-shell GNS@MSNs with Ly, and then modified the GNS@ MSNs with amino groups, which played a role in targeting tumor cells.…”
Section: Nano-oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the in vivo experimental results showed that the RGD-Bi2S3 @MSN/DOX NPs synthesized by Liu et al combined with nearinfrared radiation can effectively ablate malignant OS and prevent its recurrence (66). Similarly, Hu et al developed a new type of mesoporous silica-coated gold nanostar (GNS@ MSNs-FA) modified by folic acid (FA) with the Chinese medicine lyricine (Ly) NPs (67). In summary, the researchers utilized gold nanostars (GNS) with multiple sharp branches as the core of the nanocomposite, employing MSNs to coat the core-shell GNS@MSNs with Ly, and then modified the GNS@ MSNs with amino groups, which played a role in targeting tumor cells.…”
Section: Nano-oxidesmentioning
confidence: 99%
“…Similarly, Hu et al. developed a new type of mesoporous silica-coated gold nanostar (GNS@MSNs-FA) modified by folic acid (FA) with the Chinese medicine lyricine (Ly) NPs ( 67 ). In summary, the researchers utilized gold nanostars (GNS) with multiple sharp branches as the core of the nanocomposite, employing MSNs to coat the core-shell GNS@MSNs with Ly, and then modified the GNS@MSNs with amino groups, which played a role in targeting tumor cells.…”
Section: Research Advances In Nanoplatforms For the Treatment Of Osmentioning
confidence: 99%
“…PRN@MSN strongly inhibited the formation of microvessels in murine hemangioma models via increased ER stress, where MSN induced ER stress and PRN inhibited autophagy that was resistant to ER stress. Moreover, Hu et al (2021) integrated gold nanostars (GNS) and the antineoplastic drug lycorine (Ly) into MSNs with modified tumor-targeted folate (FA). GNS@MSNs-FA/Ly exhibited highly specific tumor growth inhibition in osteosarcoma cell tumor–bearing mice without additional side effects, among which Ly promoted mitochondrial dysfunction to interfere with ER via endoplasmic reticulum–mitochondrial contact ( Giacomello et al, 2020 ).…”
Section: Endoplasmic Reticulum Stress–inducing Nanodrugs For Cancer T...mentioning
confidence: 99%
“…To tackle these problems, a cavitation assisted endoplasmic reticulum (ER) targeted sonodynamic therapy can facilitate drug accumulation and penetration, thus elevating ER stress [ 23 , 24 ] in situ and boosting the efficacy of immunotherapy. Firstly, the tumor vascular targeted acoustic droplets evaporation (ADV) increases the aggregation and penetration of nanodroplets in the tumor microenvironment [ 25 ].…”
Section: Introductionmentioning
confidence: 99%